A Hemodynamic-Based Evaluation of Applying Different Types of Coronary Artery Bypass Grafts to Coronary Artery Aneurysms. (10th June 2020) - Wang, Haoran; Anzai, Hitomi; Liu, Youjun; Qiao, Aike; Xie, Jinsheng; Ohta, Makoto
Abstract : Coronary artery bypass grafts (CABGs), including saphenous vein grafts (SVGs) or left internal mammary artery (LIMA) grafts, are recently applied to treat coronary artery aneurysm (CAA). Surgical outcomes are considered to be related to surgical strategies (types of the bypass graft and whether CAA ligated or not) and the size of the CAA (usually characterized by diameter). However, the understanding of the relationship between the surgical outcomes and the abovementioned factors is limited. Previous studies related to CABG treatments have shown hemodynamic studies could help evaluate surgical outcomes through graft mass flow rate, wall shear stress (WSS), and oscillatory shear index (OSI). It is believed that the hemodynamic study of applying CABGs to CAA, which is not studied yet, could help us understand the different CABG surgeries. The aim of the study was to evaluate the hemodynamic differences among different surgical methods. To do this, eight three-dimensional models were constructed, representing application of SVGs and LIMA grafts to CAAs (whether ligated or not) with diameters two, three, and five times the normal diameter, to perform computational fluid dynamics (CFD) simulation. The lumped-parameter model (LPM) was coupled to the boundary of the 3D models which increase the complexity of the simulation, but it can ensure the stability of the simulation boundary conditions. The results show that SVG (no matter whether ligated or not) hemodynamic characteristics are positive, with an average high graft mass flow rate of 70 ml/min, an average WSS of 0.479 Pa, and a low OSI of 0.001. LIMA with CAA ligation has the same characteristics with higher WSS (average 1.701 Pa). The hemodynamic characteristics of LIMA without CAA ligation are negative, including high reverse mass flow rate and high OSI (0.367). The results indicate that the surgical outcomes of LIMA with CAA ligation are likely to be the best among these models. The surgical outcomes of LIMA without CAA ligation seem to be undesirable due to the high reverse mass flow and high OSI. The CAA diameter may not have a significant effect on surgical outcomes.